Improved Model Predictive Dynamic Voltage Cooperative Control Technology Based on PMU - Liu, Shu; Zhang, Lin; Wu, Zhenbin; Zhao, Jian; Li, Liang (Frontiers in Energy Research, 2022)
With the access of a large number of intermittent and fluctuating new energy sources in the low-voltage distribution network, the complex relationship between producers and consumers makes the node voltage stability and other problems in the power system increasingly prominent. Aiming at the voltage stability problem caused by the poor adaptability and low inertia of the new power system, based on the high precision measurement data of PMU, this paper uses model predictive control algorithm to realize regional voltage optimization and improve the stability of node voltage. Firstly, the voltage sensitivity matrix is calculated using PMU measurement data and grid structure state information. Secondly, active power, reactive power and voltage were taken as the input of MPC algorithm, and the optimal compensation voltage instruction was obtained by rolling optimization, and the node voltage was compensated by SVG and SVC. Finally, a simulation experiment is carried out on MATLAB/Simulink simulation platform, and the experimental results verify the correctness and effectiveness of the proposed control method.